2017
DOI: 10.1002/aic.15999
|View full text |Cite
|
Sign up to set email alerts
|

The promotion of Argon and water molecule on direct synthesis of H2O2from H2and O2

Abstract: Direct synthesis of hydrogen peroxide (H2O2) from H2 and O2 is an ideal route. H2/O2 plasma has a great potential for direct synthesis of high purity H2O2 without purification operations. However, low yield and high energy consumption limits the application of H2/O2 plasma in industry. This article reports that gas state Ar and H2O molecule serving as molecular catalysts promoted the synthesis of H2O2 from H2/O2/Ar/H2O plasma dramatically: the H2O2 yield was enhanced by 244% and the energy consumption was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Optical emission spectroscopy (OES) allows to observe atomic hydrogen (H α 656.3 nm) and atomic oxygen (OI 777.4 nm and OI 844.7 nm). For the mechanism taking place a multitude of reactions has to be considered [114]:…”
Section: Hydrogen Peroxide Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Optical emission spectroscopy (OES) allows to observe atomic hydrogen (H α 656.3 nm) and atomic oxygen (OI 777.4 nm and OI 844.7 nm). For the mechanism taking place a multitude of reactions has to be considered [114]:…”
Section: Hydrogen Peroxide Synthesismentioning
confidence: 99%
“…To improve the selectivity of the process, reactions (5)-(7) have to be facilitated, while reactions (8)- (12) need to be inhibited. The Gao group [104,114] showed that the addition of Ar and H 2 O improved the efficiency by two different routes. The addition of Ar increases the electron density by lowering the required breakdown voltage.…”
Section: Hydrogen Peroxide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, in the reaction process, the performance of H 2 O 2 production on a catalyst is largely affected by multiple relevant factors. These include H 2 and O 2 pressures, , selection of the solvents (water and alcohols), , identity of the diluent gas (N 2 , Ar, and CO 2 ), , addition of promoters (halide salts and acids), , particle effects, , and reaction temperature. In particular, it was reported that the range of H 2 /O 2 ratio was highly associated with the product selectivity during the direct synthesis process .…”
Section: Introductionmentioning
confidence: 99%
“…With the depletion of natural resources, seeking an efficient strategy to produce H 2 O 2 is important . Nowadays, many methods have been developed, including electrochemical synthesis, alcohol oxidation, direct synthesis from H 2 and O 2 , and the anthraquinone oxidation (AO) process commercially . However, the methods mentioned above have several unavoidable disadvantages: (1) abundant energy must be consumed and the amount of organic solvents used is huge; (2) mixture of H 2 and O 2 may create potential explosion hazard; (3) organic impurities used in the AO method may contaminate the generated H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%